Protecting children’s rights in Islamic law and man-made state policy: international and political journal - Laibi, Balsam Abdul Hussein (The International and Political Journal, 2025)
Islam adopted the protection of the rights of the child from his birth, took over his protection while he was a fetus, linked his lineage to his father, confirmed his inheritance and maintenance, and permitted him to make a will. The statutory laws and state policy adhered to the commandments of Islamic Sharia and United Nations treaties to provide the child with legal protection and care, where the law intervenes to create a hypothetical relationship, granting his protection and preservation. His rights and not to neglect them, we will discuss all of this in this study.